Egzistencijalistički nadahnuta lirika u Hrvatskoj, Sloveniji i Mađarskoj - Kálecz-Simon, Orsolya (Slavia Centralis, 2020)
Existentially inspired poetry in Croatia, Slovenia and HungaryIn the 1950s and 1960s, a very influential type of poetry was born in Central Europe that owes a lot to Camus, Sartre et al. While Western existentialists emphasized the need for social engagement, their Eastern colleagues concentrated on ontological questions and tried to create a literary environment isolated from ideological influences. This paper discusses the poetry of Edvard Kocbek (Slovenia), Slavko Mihalić (Croatia) and János Pilinszky (Hungary), whose most important common points are their ontological-individualistic topics, isolation of the lyric subject, the objectivist and depersonalizing tendencies, free verse and a poetic manner of speaking that is very close to live speech.
Keywords: existentialism; poetry; Central Europe; Edvard Kocbek; Slavko Mihalić; János Pilinszky